Effect of ambient humidity on the rate at which blood spots dry and the size of the spot produced. (August 2013) - Denniff, Philip; Woodford, Lynsey; Spooner, Neil
Background: For shipping and storage, dried blood spot (DBS) samples must be sufficiently dry to protect the integrity of the sample. When the blood is spotted the humidity has the potential to affect the size of the spot created and the speed at which it dries.Results: The area of DBS produced on three types of substrates were not affected by the humidity under which they were generated. DBS samples reached a steady moisture content 150 min after spotting and 90 min for humidities less than 60% relative humidity. All packaging materials examined provided some degree of protection from external extreme conditions. However, none of the packaging examined provided a total moisture barrier to extreme environmental conditions.Conclusion: Humidity was shown not to affect the spot area and DBS samples were ready for shipping and storage 2 h after spotting. The packing solutions examined all provided good protection from external high humidity conditions.